Physico-Chemical Characterization of Well Water and Their Significance with Special Reference to Public Health in Ambarnath M.I.D.C. Area, Maharashtra - Lokhande, R.S.; Sathe, C.N. (Asian Journal of Chemistry, 2010)
The MIDC area of Ambarnath is one of the highly polluted industrial belts. The paper presents results of physico-chemical studies of well water samples in order to discuss the effect of pollution on the ground water quality and the possible magnitude of health problems in Ambarnath MIDC area. The water quality parameters like colour, odour, pH, total dissolved solids, total hardness (TH), sulphates (SO42-), chlorides (Cl- ), phosphates (PO43-), total iron (Fe), calcium (Ca) and magnesium (Mg) were studied. The findings revealed that the contents of some well samples were above WHO and lSI permissible limits for drinking water. The results were discussed in the light of pollution status of the area and literature on public health aspects.